Ischemic fasciitis scalp-unusual presentation and location - Preeti J. John; Richa Mahajan; Kanwardeep Singh Kwatra; Savreet Pal Singh (Wolters Kluwer Medknow Publications, 2024)
We report a case of ischemic fasciitis in a 34-year-old male patient who presented with hard swelling on the anterior aspect of the scalp measuring 5 × 4 cm. He gave a history of wearing a tight turban constantly for many years. The lesion initially presented as redness of the skin, which gradually became a nodular swelling over 2 years. A computed tomography (CT) scan showed conical solid soft tissue attenuation mass. The operative findings were suspicious of neoplasm. However, the microscopic findings were typical of ischemic fasciitis, that is, a zonal pattern with central hypocellular fibrinoid necrosis surrounded by more cellular areas containing prominent proliferating neovessels and fibroblasts resembling granulation tissue. Ischemic fasciitis of the scalp is extremely rare, the present case occurred as a result of ischemia continuously exerted due to wearing a tight turban. This case highlights the importance of eliciting relevant case history and avoids histological misinterpretation of this pseudo-neoplastic lesion.